Blood eosinophils and inhaled corticosteroid/long-acting β-2 agonist efficacy in COPD. Issue 2 (19th November 2015) - Pavord, Ian D; Lettis, Sally; Locantore, Nicholas; Pascoe, Steve; Jones, Paul W; Wedzicha, Jadwiga A; Barnes, Neil C
Abstract : Objective: We performed a review of studies of fluticasone propionate (FP)/salmeterol (SAL) (combination inhaled corticosteroid (ICS)/long-acting β2-agonist (LABA)) in patients with COPD, which measured baseline (pretreatment) blood eosinophil levels, to test whether blood eosinophil levels ≥2% were associated with a greater reduction in exacerbation rates with ICS therapy. Methods: Three studies of ≥1-year duration met the inclusion criteria. Moderate and severe exacerbation rates were analysed according to baseline blood eosinophil levels (<2% vs ≥2%). At baseline, 57–75% of patients had ≥2% blood eosinophils. Changes in FEV1 and St George's Respiratory Questionnaire (SGRQ) scores were compared by eosinophil level. Results: For patients with ≥2% eosinophils, FP/SAL was associated with significant reductions in exacerbation rates versus tiotropium (INSPIRE: n=719, rate ratio (RR)=0.75, 95% CI 0.60 to 0.92, p=0.006) and versus placebo (TRISTAN: n=1049, RR=0.63, 95% CI 0.50 to 0.79, p<0.001). No significant difference was seen in the <2% eosinophil subgroup in either study (INSPIRE: n=550, RR=1.18, 95% CI 0.92 to 1.51, p=0.186; TRISTAN: n=354, RR=0.99, 95% CI 0.67 to 1.47, p=0.957, respectively). In SCO30002 (n=373), no significant effects were observed (FP or FP/SAL vs placebo). No relationship was observed in any study between eosinophil subgroup and treatment effect on FEV1 and SGRQ. Discussion: Baseline blood eosinophil levels may represent an informative marker for exacerbation reduction with ICS/LABA in patients with COPD and a history of moderate/severe exacerbations.